An experiential teaching-learning model for midwifery students at university level - Damaskinidis, Georgios; Eskitzis, Panagiotis (American Journal of Social Sciences and Humanities, 2025)
This research aims to render a proposed pedagogical model for midwifery students training using the principles of experiential teaching and learning by presenting research data from the 4th year undergraduate course Experiential Teaching- Learning at the Department of Midwifery, University of Western Macedonia. The research design involved an experiential-based pedagogical approach to conduct semi-structured interviews about pregnant women’s experiences of their daily lives. An interview protocol was developed by the students under the close guidance of the authors, and the research data collected were verbatim transcribed and analysed using interpretative phenomenological analysis. The study design facilitated data collection through the active engagement of the undergraduate midwifery students. The university course was transformed into a small model community with activities that reflect life in the larger society. Midwifery students developed skills useful in the decision-making process, such as inductive and deductive reasoning, by integrating the multivalent meaning of communication signs. This research training provided the students with experience as the cornerstone of education within a four-stage cycle of experiential learning. The interview protocol was developed in collaboration with the students following the five stages of the storming cycle. Following the interpretative phenomenological analysis methodology, the interview transcripts underwent a meticulous, systematic qualitative analysis. The theoretical framework of experiential learning and clinical semiotics enabled a communicative process between the student-researchers and the subjects of their training. Adopting the proposed educational model could facilitate a smooth transition between formal university midwifery training and real-world professional experience.